Navigating complexities: Confronting intriguing challenges in Wilms tumor with inferior vena cava (IVC) and atrial thrombus - Nabila Talat; Muhammad Usama Aziz; Imran Hashim; Farrukh Mahmood Sattar; Muhammad Bilal Mirza; Wajeeh Ur Rehman; Sajid Iqbal Nayyar; Muhammad Saleem; Warda Tahir (Journal of Pediatric Surgery Open)
Objective: The objective of the study was to highlight the rarity of Wilms tumor with metastatic thrombus in inferior vena cava and right atrium, emphasize the multi-disciplinary approach, meticulous surgical techniques, associated technical challenges, and the outcome. Methods: This study was conducted in the Department of Pediatric Surgery, The University of Child Health Sciences, and The Children’s Hospital Lahore, Pakistan. Out of total 183 patients with Wilms tumor presented, 17 patients showed Wilms tumor with vascular extension. A review of their data regarding demographic details, clinical presentation, radiological findings, operative management, and post-operative course was done. Results: All 17 patients of Wilms tumor with IVC thrombus were discussed in the Institutional Tumor Board meeting and after receiving neoadjuvant chemotherapy. 16 patients underwent surgical resection. One patient with distant metastasis expired before surgery. Non-anatomical hepatic resection of segment VIII has to be done in one patient. Right atrial exploration was done in 2 patients in a joint venture with a cardiac surgery team. Tragically, 2 patients passed away postoperatively. One patient had recurrent tumor thrombus for which he had extensive chemotherapy followed by thrombectomy. The remaining 13 patients are doing fine on follow-up with the longest follow-up of 5 years. Conclusion: Our small number of patients describe the rarity of Wilms tumor with IVC thrombus. Neoadjuvant chemotherapy has gained success in the regression of thrombus which is followed by surgical excision. IVC Thrombectomy after taking proximal and distal vascular control is quite challenging for surgeons not frequently dealing with these cases. Cardiac surgery aid is also required in cases of intra-atrial extension of thrombus. Multidisciplinary management is essential for improved outcomes.